Data arenas: The relational dynamics of data activism - Bartosz Ślosarski (Big Data & Society)
The article proposes the theoretical category of data arenas as a relational field for strategic actors in diverse areas of the contentious politics of data (Beraldo and Milan, 2019). The paper argues that the conceptualization of data activism needs to be related to the immediate data arena in which the action takes place, in order to select the interactive opportunities and threats for emerging data-driven repertoires of action. To fully work through the relational dynamics of data activism, it is necessary to move from a conceptualization of data infrastructure to the notion of data arenas as an ‘open-ended bundle of rules and resources that allows certain kinds of interaction to proceed’ (Jasper, 2006: 141). Using the case of environmental data activism, I highlight four key dimensions to study: (a) strategic use of data as capital that differentiates and positions actors, as well as influences their further choices; (b) practices of defining the boundaries of the problem on which the arena focuses and outlining the pool of actors who participate in the process of solving it; (3) sets of relationships among the outlined pool of actors which represent opportunities and threats for the actors, related to the position they occupy within an arena; and (4) power as the ability to control and shape an arena. Data arena approach shed new light on data activism as a relational practice, combining the latest developments in research on data contexts and the political situatedness of data with the emerging field of research on data activism.